2017
DOI: 10.3762/bjnano.8.36
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring bifunctional hybrid organic–inorganic nanoadsorbents by the choice of functional layer composition probed by adsorption of Cu2+ ions

Abstract: Spherical silica particles with bifunctional (≡Si(CH2)3NH2/≡SiCH3, ≡Si(CH2)3NH2/≡Si(CH2)2(CF2)5CF3) surface layers were produced by a one-step approach using a modified Stöber method in three-component alkoxysilane systems, resulting in greatly increased contents of functional components. The content of functional groups and thermal stability of the surface layers were analyzed by diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, and 13C and 29Si solid-state NMR spectroscopy revealing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Moreover, it is known that thiol groups are easily oxidized to form disulfide bonds 25 , 26 that are no longer capable of ion-exchange interactions, which decrease their sorption capacity towards many metal ions 27 . Recently it has been demonstrated that introduction of an additional alkyl function into the ligand layer is capable to limit the unwanted interactions and stabilize single functional groups 28 . Therefore it appeared plausible that expanding the range of application for such particles could be achieved by creating mono- as well as bifunctional layers, containing thiol, methyl and/or propyl groups on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is known that thiol groups are easily oxidized to form disulfide bonds 25 , 26 that are no longer capable of ion-exchange interactions, which decrease their sorption capacity towards many metal ions 27 . Recently it has been demonstrated that introduction of an additional alkyl function into the ligand layer is capable to limit the unwanted interactions and stabilize single functional groups 28 . Therefore it appeared plausible that expanding the range of application for such particles could be achieved by creating mono- as well as bifunctional layers, containing thiol, methyl and/or propyl groups on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…The divergence in elemental analysis and titration of NH 2 –/SiO 2 may result from the inaccessibility of the groups or their washing off in the acidic medium. As previously reported, , the presence of additional trifunctional silane with an organic group during the sol–gel transformations of TEOS and APTES affects the speed of co-condensation. There are simultaneous reactions of hydrolysis, condensation, and dissolution proceeding in the alkaline medium created by amino groups .…”
Section: Resultsmentioning
confidence: 52%
“…The one-pot approaches described in ref , were used to synthesize two types of samples: amino–/silica (NH 2 –/SiO 2 ) and amino–/phenyl–/silica (NH 2 –/C 6 H 5 –/SiO 2 ). Briefly, TEOS (0.018 mol) and APTES (0.006 mol) [or APTES (0.003 mol) with PhTES (0.003 mol)] were mixed with ethanol (100 mL).…”
Section: Methodsmentioning
confidence: 99%
“…It seems that chelation within a Cyclen ring is also contributing to the mechanism of uptake. This indicates a considerable difference for the uptake in mesoporous nanoparticles compared to that of dense nanoparticles, where coordination of metal cations most often can be related to complexation in the monolayer on the surface [14] . The mapping of Ni(II) on E‐P1’ 75/25 PMO NPs and its quantification (Table S5 and Table S7) was performed with EDS (Figures S17–S18) after adsorption of an aqueous solution of Ni(II) at 0.5 and 10 mM initial metal concentration, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates a considerable difference for the uptake in mesoporous nanoparticles compared to that of dense nanoparticles, where coordination of metal cations most often can be related to complexation in the monolayer on the surface. [14] The mapping of Ni(II) on E-P1' 75/25 PMO NPs and its quantification (Table S5 and Table S7) was performed with EDS (Figures S17-S18) after adsorption of an aqueous solution of Ni(II) at 0.5 and 10 mM initial metal concentration, respectively. We observed a homogeneous distribution of Ni(II) in the nanorods with an adsorption of 0.46 mmol • g À 1 and 0.94 mmol • g À 1 of Ni(II), respectively.…”
Section: Adsorption Studies Of Ni(ii) and Co(ii)mentioning
confidence: 99%